2019
DOI: 10.2169/internalmedicine.0813-18
|View full text |Cite
|
Sign up to set email alerts
|

A Case Series of Acute Kidney Injury During Anti-tuberculosis Treatment

Abstract: ObjectiveThe standard anti-tuberculosis (TB) regimen occasionally causes acute kidney injury (AKI). The major etiology is rifampicin-induced acute interstitial nephritis. However, the standard management of AKI induced by anti-TB drugs has yet to be established. Methods We retrospectively reviewed patients with TB who developed AKI after starting standard anti-TB treatment between 2006 and 2016 at a single TB center. The clinical characteristics and the management are described. Results Among 1,430 patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…This is the first prospective study to investigate the risk of AKI among patients receiving anti-TB treatment by regularly monitoring their renal function; we report three major findings. First, the incidence of AKI during anti-TB treatment [13][14][15][16]20]. Four studies enrolled patients receiving anti-TB treatment [13][14][15]20], and two focused on patients receiving RIF [8,16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the first prospective study to investigate the risk of AKI among patients receiving anti-TB treatment by regularly monitoring their renal function; we report three major findings. First, the incidence of AKI during anti-TB treatment [13][14][15][16]20]. Four studies enrolled patients receiving anti-TB treatment [13][14][15]20], and two focused on patients receiving RIF [8,16].…”
Section: Discussionmentioning
confidence: 99%
“…First, the incidence of AKI during anti-TB treatment [13][14][15][16]20]. Four studies enrolled patients receiving anti-TB treatment [13][14][15]20], and two focused on patients receiving RIF [8,16]. The incidence of AKI in Romania [13], Japan [20], and Taiwan ranges from 0.05 to 10.4%.…”
Section: Discussionmentioning
confidence: 99%
“…A number of case series have also reported acute renal failure in the context of rifampin therapy [ 25–30 ]. One series reported 41 cases of biopsy-proven ATIN [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the patient was asymptomatic, ATIN diagnosis was achieved based on the findings in urine sediment, the temporal relationship with the administration of anti-tuberculous drugs, and the fact that rifampicin is the drug most associated with this pathology. (8,16) Some publications on this subject can be found in the literature. Chang et al (5), in a study conducted in Taiwan, studied acute kidney disease in patients treated with the four-drug tuberculosis regimen and found that it occurred in 7.1% of patients, of whom 11% developed the disease after first exposure to rifampicin.…”
Section: Discussionmentioning
confidence: 99%